Logic and Abduction: Cognitive Externalizations in Demonstrative Environments - Magnani, Lorenzo (THEORIA. An International Journal for Theory, History and Foundations of Science, 2009)
In her book Abductive Reasoning Atocha Aliseda (2006) stresses the attention to the logical models of abduction, centering on the semantic tableaux as a method for extending and improving both the whole cognitive/philosophical view on it and on other more restricted logical approaches. I will describe the importance of increasing logical knowledge on abduction also taking advantage of some ideas coming from the so-called distributed cognition where logical models are seen as forms of cognitive externalizations of preexistent in-formal human reasoning performances